2022
DOI: 10.3389/fevo.2022.986459
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality can affect ecological interactions between fishes of different thermal guilds

Abstract: Seasonality could play a crucial role in structuring species interactions. For example, many ectotherms alter their activity, habitat, and diet in response to seasonal temperature variation. Species also vary widely in physiological traits, like thermal preference, which may mediate their response to seasonal variation. How behavioral responses to seasonality differ between competing species and alter their overlap along multiple niche axes in space and time, remains understudied. Here, we used bulk carbon and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 114 publications
0
10
0
Order By: Relevance
“…We also note that the equations developed to examine the relationship between swimming speed and accelerometer data were based on lab trials conducted at a single water temperature (12 °C;[ 51 ]) and should be recalibrated across a range of environmentally relevant temperatures that Lake Trout occupy. Our estimates of average winter swim speed from the array (winter1: ~7.5 m min − 1 ; winter2: ~4.5 m min − 1 ) were comparable to, although slightly higher than, those for Lake Trout from a similar telemetry study in a southern lake, and which also demonstrated similar variation in swim speed from one winter to the next (winter1: 3.0 m min − 1 ; winter2: 5.8 m min − 1 ) [ 55 ].…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…We also note that the equations developed to examine the relationship between swimming speed and accelerometer data were based on lab trials conducted at a single water temperature (12 °C;[ 51 ]) and should be recalibrated across a range of environmentally relevant temperatures that Lake Trout occupy. Our estimates of average winter swim speed from the array (winter1: ~7.5 m min − 1 ; winter2: ~4.5 m min − 1 ) were comparable to, although slightly higher than, those for Lake Trout from a similar telemetry study in a southern lake, and which also demonstrated similar variation in swim speed from one winter to the next (winter1: 3.0 m min − 1 ; winter2: 5.8 m min − 1 ) [ 55 ].…”
Section: Discussionmentioning
confidence: 84%
“…We also observed significantly lower rates of activity in the second winter of the study, which followed a prolonged fall period that lasted three weeks longer than in the previous year. Differences in Lake Trout winter movement rates were also observed between years in a similar study at a more southern lake [ 55 ], and may reflect the energetic constraints imposed by the demands of the preceding fall spawning season.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations